Pengaruh Media Pembelajaran Gimkit untuk Meningkatkan Hasil Belajar Siswa Kelas X pada Mata Pelajaran IPA Biologi di SMA Negeri 1 Kadugede (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine how the use of Gimkit as a learning medium contributed to better learning outcomes for 10th grade students in science and biology at SMA Negeri 1 Kadugede. This study used a quantitative method with a quasi-experimental design. The research sample consisted of two classes, namely the experimental class that used Gimkit and the control class that used conventional learning methods. The population used was grade X with a total of 394 students, and the sample consisted of 72 students. The research instruments consisted of pretest and posttest questions used to measure learning outcomes and a questionnaire used to determine students' reactions to the use of Gimkit. To analyze the data, normality, homogeneity, paired sample t-test, and independent tests were used. The results of this study indicate that students' learning outcomes in science and biology improved both before and after using the Gimkit media. The use of the Gimkit learning medium is more effective than conventional methods. This is evidenced by the increase in pretest and posttest scores in the experimental class from 58.61 to 74.17. This indicates a significant improvement in learning outcomes after using the Gimkit medium, with an increase of 15.56.